Crucial Role of Reactive Oxygen Species (ROS) for the Proapoptotic Effects of Indirubin Derivatives in Cutaneous SCC Cells - Jiaqi Zhu; Peter Langer; Claas Ulrich; Jürgen Eberle (MDPI AG, 2021)
Efficient drugs are needed for countering the worldwide high incidence of cutaneous squamous cell carcinoma (cSCC) and actinic keratosis. Indirubin derivatives represent promising candidates, but their effects in cSCC cells have not been reported before. Here, we investigated the efficacy of three indirubin derivatives (DKP-071, -073 and -184) in four cSCC cell lines. High efficacy was seen in SCL-I, SCL-II, SCC-12 and SCC-13, resulting in up to 80% loss of cell proliferation, 60% loss of cell viability and 30% induced apoptosis (10 µM). Apoptosis was further enhanced in combinations with TNF-related apoptosis-inducing ligand (TRAIL). Induction of reactive oxygen species (ROS) appeared as critical for these effects. Thus, antioxidative pretreatment completely abolished apoptosis as well as restored cell proliferation and viability. Concerning the pathways, complete activation of caspases cascades (caspases-3, -4, -6, -7, -8 and -9), loss of mitochondrial membrane potential, activation of proapoptotic PKCδ (protein kinase C delta), inhibition of STAT3 (signal transducer and activator of transcription 3), downregulation of antiapoptotic XIAP (X-linked inhibitor of apoptosis protein) and survivin as well as upregulation of the proapoptotic Bcl-2 protein Puma and the cell cycle inhibitor p21 were obtained. Importantly, all activation steps were prevented by antioxidants, thus proving ROS as a master regulator of indirubins' antitumor effects. ROS induction presently develops as an important issue in anticancer therapy.